Decreased submandibular adiponectin is involved in the progression of autoimmune sialoadenitis in non‐obese diabetic mice. (19th November 2013) - Su, Y‐C; Xiang, R‐L; Zhang, Y; Ding, C; Cong, X; Guo, X‐H; Yang, N‐Y; Hua, H; Wu, L‐L; Yu, G‐Y
<x xml:space="preserve">Abstract</x> Objective To investigate a possible role of adiponectin in the pathogenesis of autoimmune sialoadenitis in non‐obese diabetic (NOD) mouse model of Sjögren's syndrome. Materials and Methods Expression of adiponectin and its receptors (AdipoR1/2) was detected by PCR, immunoblotting, or immunofluorescence. The level of adiponectin was quantified by ELISA. Adiponectin‐related signaling molecules and pro‐inflammatory cytokines were examined by PCR or immunoblotting. Apoptosis was evaluated by TUNEL staining, flow cytometry, and caspase 3 activation. Results Adiponectin and AdipoR1/2 mRNA and protein were expressed in submandibular glands. Adiponectin immunostaining was widely diffused in the cytoplasm of acinar and ductal cells. AdipoR1 was mainly distributed in acinar cytoplasm, while AdipoR2 was predominantly located at acinar cell membrane. Submandibular adiponectin levels were reduced during the progression of autoimmune sialoadenitis in 7‐, 14‐, and 21‐week‐old NOD mice, while AdipoR1/2 levels were unchanged. The levels of phosphorylated adenosine monophosphate‐activated protein kinase, extracellular signal‐regulated kinase 1/2, and p38 mitogen‐activated protein kinase were decreased, while interferon (IFN)‐γ and glandular apoptosis were temporally increased at all time points. Moreover, exogenous adiponectin supplement inhibited, whereas neutralizing endogenous adiponectin by its antibody promoted IFN‐γ‐induced apoptosis and caspase 3 activation in cultured submandibular acinar cells. Conclusions Adiponectin plays a protective role on submandibular cells. Decreased adiponectin might promote glandular destruction in autoimmune sialoadenitis.